Metabolism of the Marine Phycotoxin PTX-2 and Its Effects on Hepatic Xenobiotic Metabolism: Activation of Nuclear Receptors and Modulation of the Phase I Cytochrome P450 - Alarcan, Jimmy (Toxins (Basel), 2017)
PTX-2 is a marine biotoxin frequently found in shellfish that can lead to food intoxication in humans. Information regarding PTX-2 metabolism is scarce, and little is known of its effect on xenobiotic-metabolizing enzymes (XME) or its molecular pathways. The aim of this study was consequently to examine PTX-2 Phase I metabolism using rat and human liver S9 fractions, and also to assess the capability of PTX-2: (i) to modulate the gene expression of a panel of Phase I (CYP450) and II (UGT, SULT, NAT, and GST) enzymes, as well as the Phase III or 0 (ABC and SLCO) transporters in the human hepatic HepaRG cell line using qPCR; (ii) to induce specific CYP450 in HepaRG cells measured by immunolabeling detection and the measurement of the cells’ activities; and (iii) to activate nuclear receptors and induce CYP promoter activities in HEK-T and HepG2 transfected cell lines using transactivation and reporter gene assay, respectively. Our results indicate that PTX-2 hydroxylation occurred with both rat and human S9 fractions. Whereas PTX-2 mostly upregulated the gene expression of CYP1A1 and 1A2, no induction of these two CYP activities was observed. Lastly, PTX-2 did not act as an agonist of CAR or PXR. Due to its effects on some key XME, more attention should be paid to possible drug–drug interactions with phycotoxins, especially as shellfish can accumulate several phycotoxins as well as other kinds of contaminants.